MODEL PELAYANAN PAJAK KENDARAAN BERMOTOR YANG BERDAMPAK PADA KEPUASAN MASYARAKAT WAJIB PAJAK DI SAMSAT KOTA BOGOR - Irenda Putri Utami; Rita Rahmawati; Ginung Pratidina (Jurnal Governansi, 2018)
Public service is all types of activities the do by the central government and regional to meet all kinds of basic necessities or also in order to implement the act.Tax is making a major contribution to of the republic of indonesia this.Vehicle tax get better itself is tax are part types of taxes province that is occupied for their household needs their own province.Objectives of the study are aimed to know and to also analyzed the hour by hour a model that they are located in operation of samsat kota bogor it is also determine the influence of the quality of act to provide service for of community satisfaction tax payers in operation of samsat kota bogor.Was used in the study research methodology associative by the use of quantitative data .Data collection was carried out by means of observation , the interviews and also the spread of other of any economic indicators .Pengumpalan the data is provided by way of the population as many as 1450 and the research sample as many as 94 respondents in the present study.Of the study is such an amount for variables x 3.34 and belonging to the criteria for good enough . While for variables y got as much as 3.31 belonging to the criteria for good enough also .In the test correlation rank spearmen known such an amount 0.976 which means there is a correlation between extremely strong and positive varaibel x and y variables .While for the coefficient of determination obtained 95,2 % the figure of .It was discovered that the variable x contributed 95 % for variables y or customer satisfaction .Keyword: Service Quality, Customer Satisfaction.